Anti-blackness and public schools in the border South : policy, politics, and protest in St. Louis, 1865-1972 - Weathersby, Claude; Davis, Matthew D. (History of education, 2019)
"This new book on Black public schooling in St. Louis is the first to fully explore deep racialized antagonisms in St. Louis, Missouri. It accomplishes this by addressing the white supremacist context and anti-Black policies that resulted. In addition, this work attends directly to community agitation and protest against racist school policies. The book begins with post-Civil War schooling of Black children to the important Liddell case that declared unconstitutional the St. Louis Public Schools. The judicial wrangling in the Liddell case, its aftermath, and community reaction against it awaits a next book by the authors of Anti-blackness and public schools"--